2008
DOI: 10.1007/s00011-007-7190-3
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide microarray analysis reveals anti-inflammatory target genes of paeonol in macrophages

Abstract: Our results demonstrate that paeonol has extensive inhibitory effects on the regulation of inflammation associated gene expression by LPS in macrophages. In addition, the predominant effect of paeonol among the tested compounds suggests that paeonol may be a major ingredient for the anti-inflammatory effect of paeony root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 36 publications
(40 reference statements)
1
35
0
Order By: Relevance
“…Recently, Pae has been reported to have an immunoregulatory effect, treatment with Pae inhibited LPS-induced nitric oxide production and IL-6 mRNA expression in macrophages [6,7]. Furthermore, Pae was found to significantly protect against bacillus Calmette-Guérin plus LPSinduced liver injury via modulating TNF-α and IL-6 mRNA expression in mice [8].…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Pae has been reported to have an immunoregulatory effect, treatment with Pae inhibited LPS-induced nitric oxide production and IL-6 mRNA expression in macrophages [6,7]. Furthermore, Pae was found to significantly protect against bacillus Calmette-Guérin plus LPSinduced liver injury via modulating TNF-α and IL-6 mRNA expression in mice [8].…”
Section: Introductionmentioning
confidence: 94%
“…TNFα, IFN-γ and IL-2, in TGP-treated RA patients, so in their counterparts in rheumatoid arthritis animal models [17][18][19]. Recently, gene array assay shows that TGP reduce some inflammatory cytokine expression [12]. In addition, TGP have been found to induce regulatory CD4 + CD25 + T cells by increasing Foxp3 demethylation in lupus CD4 + T cells [15].…”
Section: Introductionmentioning
confidence: 96%
“…Paeoniflorin exhibits both anti-inflammatory and immune-regulatory effects [11][12][13][14]. Recently, total glucosides of paeony (TGP), an active compound extracted from Paeony root that is mainly composed of paeoniflorin (>90%), has been reported to have a clinically significant therapeutic effect on RA [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…An experiment conducted by Fu et al discovered a lower level of urinary albumin and ameliorated glomerular hypertrophy, together with decreased macrophage infiltration and inflammatory factor production in Paeoniflorin-treated rats (16). Also, Huang et al revealed TLR as one of the paeonol target genes relevant to the anti-inflamatory effect (17). Therefore, the former evidence implicated that Paeoniflorin might mediate the inflammatory response via the TLRs signaling pathway in DN.…”
Section: Introductionmentioning
confidence: 99%